2019
DOI: 10.1292/jvms.18-0537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic background on responses to superovulation in Japanese Black cattle

Abstract: We investigated the effects of genetic background on the responses to superovulation in Japanese Black cattle. The genotype frequencies of GRIA1 and FSHR relating to ovulation and follicular development in each of the major bloodlines—Tajiri, Fujiyoshi, and Kedaka—were analyzed. The Tajiri line had the lowest frequency of G allele homozygosity of c.710A>G in GRIA1 among the three bloodlines, and deviation from Hardy–Weinberg equilibrium was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…Mutations in the GRIA1 gene have been described to be involved with superovulation rates in Wagyu cattle [ 14 ]. In addition to that, a study conducted by Hirayama and colleagues [ 15 ] identified that levels of plasma anti-Müllerian hormone (AMH) concentration, age in months, repeated superovulation, mutations in the FSHR gene and bloodlines had significant effects on the responses to superovulation. To minimize the effect of the genetic variation in response to SOV protocols, we used only animals with a greater percentage of the Tajima line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the GRIA1 gene have been described to be involved with superovulation rates in Wagyu cattle [ 14 ]. In addition to that, a study conducted by Hirayama and colleagues [ 15 ] identified that levels of plasma anti-Müllerian hormone (AMH) concentration, age in months, repeated superovulation, mutations in the FSHR gene and bloodlines had significant effects on the responses to superovulation. To minimize the effect of the genetic variation in response to SOV protocols, we used only animals with a greater percentage of the Tajima line.…”
Section: Discussionmentioning
confidence: 99%
“…Sugimoto et al [ 14 ] have identified an association of a single nucleotide polymorphism (SNP) in the glutamate ionotropic receptor AMPA type subunit 1 ( GRIA1 ) with ovulation rates in Wagyu cattle. Hirayama et al [ 15 ] have further characterized variations in the allele frequency of GRIA1 among different lines of Wagyu, indicating an effect of the genetic background on the responses to superovulation. Therefore, the selection of animals with the allele favorable to a superovulation protocol (SOV) response might improve reproductive success in Wagyu cattle.…”
Section: Introductionmentioning
confidence: 99%
“…The current work demonstrated that mRNA expression of FSHR in blood prior to superstimulation predicted the ability of Holstein cows to respond better to superovulatory FSH treatment, reflected in higher number of total embryos, higher number of total transferable embryos and total grade 1 embryos. Correlations of FSHR gene with superovulation response in different breeds of cattle have been reported previously (Hirayama et al, 2019;Marson et al, 2008).…”
Section: Discussionmentioning
confidence: 90%
“…Hirayama et al. (2019) reported that number of transferable embryos collected from Japanese black cows was significantly higher in the group heterogenous for c.337C > G in FSHR. More specifically, variations of FSHR SNP may cause functional changes in G‐protein and dimensional structure of the receptor altering its response to FSH (Yang et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These variability have been attributed to gonadotrophin preparation with differences LH:FSH activities [5][6][7][8][9] and its protocols for treatments [10,11]. In addition, antral follicle count and AMH level are contributed to these variability's [12,13]. Selection of candidate donor's cows for embryos production based on AMH level will reduce this variability [14].…”
Section: Introductionmentioning
confidence: 99%